Pengaruh Jumlah Kunjungan Wisatawan, Lama Tinggal dan Tingkat Hunian Hotel Terhadap Pajak Hotel Restoran dan Pertumbuhan Ekonomi di Kota Denpasar - Rediteani, Ni Made; Setiawina, Nyoman Djinar (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 1, Januari 2018 (pp. 1 - 211), 2018)
ABSTRACT Tourism industry is one of the industries that contributes in the economic growth of Indonesia. The tourism sector is considered equally to exports that can contribute to the economic growth of a region. The purpose of this research was analyzing the impact of the number of tourist arrivals, length of stay, and room occupancy rate and economic growth in the Denpasar city. The type of data used in this research was secondary data from 1998 to 2015. The research used Non-participant observation and in-depth interviews as the data collection methods. Path analysisoand sobel test to analyze indirect influence through intervening variable were used for the data analysis technique. Based on the analysis obtained the result that the number of tourist arrivals and length of stay have a direct and significant effect on hotel restaurant tax, whereas the room occupancy rate has no direct and significant effect. The number of tourist arrivals has no direct effect on economic growth, whereas the length of stay, room occupancy rate, and hotel restaurant taxes have a direct and significant effect on economic growth. Hotel and restaurant taxes are the intervening variable of the number of tourist arrivals to economic growth.